Audiological evaluation in patients with psoriasis - Maha Elsayed Ahmed; Abdel-Khalek Hassan Younes; Mohamed Mohamed Elmoursy; Mahmoud Abd Elsabour Makki (Wolters Kluwer Medknow Publications, 2021)
Background Psoriasis is a multisystem, immune disorder driven by inflammatory processes, characterized by skin and joint manifestations, and may be associated with hearing loss. Aim To assess the hearing function in patients with psoriasis and if psoriasis could cause sensorineural hearing loss (SNHL). Patients and methods A total of 50 patients with psoriasis and 50 apparently healthy controls matched for age and sex were included in a cross-sectional comparative study between May 2017 and April 2018. Medical history of patients was taken. Demographics, type of psoriasis, and disease severity evaluated by PASI score were assessed. All patients who were included in this study provided a complete history and audiological history. All patients underwent otoscopic examination, pure tone audiometry, speech audiometry, and immittancemetry including tympanometry and acoustic reflexes. Results There was no statistically significant difference in age or sex for patients with psoriasis and the control group. Eight patients with psoriasis showed impaired hearing function with significant longer duration with psoriasis and older age more than 20 years old in comparison with the rest of the patient. Conclusion Psoriasis is a chronic inflammatory immune-mediated skin disease with estimated prevalence in Upper Egypt at a rate of 0.19% of skin diseases. There were eight (16%) patients who had SNHL in psoriatic group in comparison with three (6%) cases in nonpsoriatic group. There was a statistically significant difference for the age and the duration of psoriasis in relation to hearing loss. SNHL increased with age in psoriatic patients much more than in healthy controls.